Regulatory roles of ferroptosis-related non-coding RNAs and their research progress in urological malignancies - Wang, Shijin; Jiang, Bowen; Xie, Deqian; Li, Xiunan; Wu, Guangzhen (Frontiers in Genetics, 2023)
The abnormal proliferation of tumor cells and evasion of cell death are important biological features of malignant tumors. These features plausibly explain the lethality, aggressive metastasis, and treatment resistance of tumors (4). Ferroptosis is a new form of RCD characterized by the accumulation of reactive oxygen species (ROS) and depletion of polyunsaturated fatty acids in the plasma membrane when the intracellular environment is specifically disturbed, ultimately leading to iron-dependent oxidative cell death. Its morphological, genetic, and biochemical manifestations differ from those of autophagy, apoptosis, necrosis, and pyroptosis (5-8).Non-coding RNAs (ncRNAs) can be roughly classified into microRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs) according to their length and morphology (9, 10). With the widespread application of high-throughput sequencing technology, many ncRNAs have been found to be involved in the pathophysiological processes of multiple diseases, and previously unappreciated ncRNAs have been revitalized (11, 12). Generally, miRNAs are endogenous single-stranded small molecule RNAs comprising approximately 22 nucleotide sequences. Extracellular miRNAs are transported to recipient cells through exosomes, small vesicles, apoptotic bodies, and base pairs with the 3' untranslated region of the target mRNA to inhibit its transcription and translation (16-18). LncRNA is a molecule longer than 200 nucleotides that does not encode protein (19, 20). Recent studies have found that lncRNAs participate in biological processes, such as the proliferation and differentiation of tumor cells, by regulating transcription and translation (21-23). lncRNAs regulate tumor development by exerting competing endogenous RNA actions through sponge miRNAs (24-26). Because circRNAs are stable and unaffected by exonucleases, they are more suitable diagnostic and prognostic markers than lncRNAs and miRNAs. Moreover, circRNAs have other biological functions; for example, in the nucleus, they can participate in transcriptional regulation and regulate gene expression. In the cytoplasm, they can be adsorbed by sponges and interact with RNA-binding proteins to promote or suppress tumors (27). Although several treatment strategies are available, patients with advanced disease usually have poor prognosis and low survival rate because of treatment insensitivity and susceptibility to recurrence. Therefore, it is necessary to develop novel diagnostic and therapeutic methods.